Potential role of lycopene in targeting proprotein convertase subtilisin/kexin type-9 to combat hypercholesterolemia - KHAN, IMRAN; Alvi, Sahir Sultan; Ansari, Irfan A.; Khan, IMRAN; Iqbal, Johar; Khan, M. Salman (My University, 2017)
Proprotein convertase subtilisin/kexin type 9 (PCSK-9) is a serine protease of the proprotien convertase (PC) family that has profound effects on plasma low density lipoprotein cholesterol (LDL-C) levels, the major risk factor for coronary heart disease (CHD), through its ability to mediate LDL receptor (LDL-R) protein degradation and reduced recycling to the surface of hepatocytes. Thus, the current study was premeditated not only to evaluate the role of lycopene in targeting the inhibition of PCSK-9 via modulation of genes involved in cholesterol homeostasis in HFD rats but also to examine a correlation between HFD induced inflammatory cascades and subsequent regulation of PCSK-9 expression. Besides the effect of lycopene on hepatic PCSK-9 gene expression, PPI studies for PCSK-9-Lycopene complex and EGF-A of LDL-R were also performed via molecular informatics approach to assess the dual mode of action of lycopene in LDL-R recycling and increased removal of circulatory LDL-C. We for the first time deciphered that lycopene treatment significantly down-regulates the expression of hepatic PCSK-9 and HMGR, whereas, hepatic LDL-R expression was significantly up-regulated. Furthermore, lycopene ameliorated inflammation stimulated expression of PCSK-9 via suppressing the expression of inflammatory markers. The results from our molecular informatics studies confirmed that lycopene, while occupying the active site of PCSK-9 crystal structure, reduces the affinity of PCSK-9 to complex with EGF-A of LDL-R, whereas, atorvastatin makes PCSK-9-EGF-A complex formation more feasible than both of PCSK-9-EGF-A alone and Lycopene-PCSK-9-EGF-A complex. Based on above results, it can be concluded that lycopene exhibits potent hypolipidemic activities via molecular mechanisms that are either identical (HMGR inhibition) or distinct from that of statins (down-regulation of PCSK-9 mRNA synthesis). To the best of our knowledge, this is the first report that lycopene has this specific biological property. Being a natural, safer and alternative therapeutic agent, lycopene could be used as a complete regulator of cholesterol homeostasis and ASCVD.